Darier and Hailey‐Hailey disease: update 2021. (18th October 2021) - Rogner, Danielle Franziska; Lammer, Judith; Zink, Alexander; Hamm, Henning
Summary: The autosomal‐dominant genodermatoses Darier disease and Hailey‐Hailey disease present special challenges to dermatologists. Despite their similar pathogenesis featuring impaired adhesion of suprabasal keratinocytes as a result of defective ATPases in epidermal calcium channels, the two diseases differ considerably in clinical presentation and therapeutic options. Darier disease is characterized by reddish brown, keratotic papules in seborrheic and intertriginous areas, which may coalesce into extensive lesions. Individuals affected with Hailey‐Hailey disease primarily develop intertriginous papulovesicles and small blisters, which often evolve into erythematous plaques with erosions and painful fissures. Quality of life is significantly reduced because of complaints (itch, burning sensation, pain), body malodor and chronicity. Therapeutic options remain limited. Antiseptics and intermittent topical corticosteroids are a cornerstone of therapy, and systemic anti‐infective treatment is often required in cases of superinfection. Ablative surgical interventions such as dermabrasion and CO2 laser surgery can lead to long‐term remissions in intertriginous Hailey‐Hailey disease, while temporary relief may also be achieved by intralesional injections of botulinum toxin. Of the systemic medications available for Darier disease, acitretin, which is approved for this purpose, has the best supporting evidence. The efficacy of immunosuppressants and immune modulators is inconsistent. Low‐dose naltrexone produces more satisfactory results in Hailey‐Hailey than Darier disease. The present CME article summarizes current knowledge of the two dermatoses, taking recent developments into account.